Rancang Bangun Alat Pengendali Lampu pada Sistem Informasi Penjadwalan Menggunakan Arduino Uno R3 Berbasis Web - Ismanto Ismanto; Sulistiyasni Sulistiyasni; Dewi Erla Mahmudah (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2017)
The use of electric power must be wise and efficient. For that we need a way to control the use of electrical power to be automatic and easy. The author tries to make design of light controller in scheduling information system using Arduino Uno R3 web based. Design of light controller tool on web-based scheduling information system is using prototype method. Where the cycle of design and development is quite simple that is through 3 stages starting from Listen to Customer,Design and Building and for the next Test Drive and Evaluations.The result of design of light controller in scheduling information system using Arduino Uno R3 web based after tested by 15 testers product obtained product value 92.66 which means above the minimum value of the product set is 75. And usability test using questionnaire method to assess Aspects of Learnability, Efficiency, Memorability, Errors and Satisfactions (LEMES) where the lowest average value of all aspects is 4.58 which means above the minimum limit ie the middle value is based on the Likert scale 1 - 5.